Enhanced photocatalytic properties of Bi4O5Br2 by Mn doping: a first principles study. (13th July 2018) - Zhang, Weibin; Chen, Shanjun; He, Meilin; Zhu, Gangqiang; Yang, Woochul; Tian, Yonghong; Zhang, Zhijun; Zhang, Shaolin; Zhang, Fuchun; Wu, Qingfeng
Abstract: We investigated the improvements in the photocatalytic properties of Bi4 O5 Br2 after Mn-doping via first principles calculations. Based on the formation energy calculation, transition metals replaced Bi atoms with a coordination bond of 4. Importantly, the Mn-doped Bi4 O5 Br2 has the lowest band gap among transition metal-doped Bi4 O5 Br2 . The key factors underlying the improvements in photocatalytic efficiency are estimated as follows. First, the band gap decreased from 2.38 eV in the pristine case to 1.88 eV in the six Mn-doped Bi4 O5 Br2 case resulting in a shift of the photon absorption edge to lower energy. Second, the absorption coefficient in the visible light range obviously increases with Mn-doped Bi4 O5 Br2 . Third, the relative mass ratio of photoinduced electrons and holes increases with Mn concentration resulting in a higher efficiency of charge carrier separation. Therefore, it is reasonable to believe that the photocatalytic efficiency of Bi4 O5 Br2 can be improved via Mn-doping. Our work provides a reasonable rationale for choosing Mn as a dopant—this can help experimental work and explain the improvements in photocatalytic efficiency.